SUMBANGAN BINA IMAN ANAK KATOLIK BAGI PERKEMBANGAN IMAN ANAK - Kurniati, Monika; Supriyadi, Agustinus (CREDENDUM: Jurnal Pendidikan Agama, 2025)
Catholic Children's Faith Formation Program (BIAK) is a faith development program proposed by the Catholic Church for Catholic children’s faith dan attitudes development.This faith formation is carried out for children aged 5-12 years.This is done for the growth and development of the Catholic children's faith and attitudes.Mater Dei Parish in Madiun city has a Catholic Children's Faith Formation (BIAK) program especially for the children aged 5-12 years.This study aims to identify the understanding of both Catholic children’s faith formation instructors and parents regarding the contribution of the Catholic children’s faith formation activities on the children’s faith and attitudes development. This study was conducted using a qualitative method approach.Data collection was carried out using structured and individual interview techniques.The informants for this study were children’s faith formation instructors and the parents of the children. The results of the study indicated that Catholic chlidren’s faith formation program has a significan contribution on the children’s faith and attitudes development.